Injectable Bone Cement Reinforced with Gold Nanodots Decorated rGO‐Hydroxyapatite Nanocomposites, Augment Bone Regeneration. Issue 14 (15th January 2023) - Chopra, Vianni; Thomas, Jijo; Kaushik, Swati; Rajput, Swati; Guha, Rajdeep; Mondal, Bidya; Naskar, Sudip; Mandal, Dipankar; Chauhan, Gaurav; Chattopadhyay, Naibedya; Ghosh, Deepa
Abstract: Interest in the development of new generation injectable bone cements having appropriate mechanical properties, biodegradability, and bioactivity has been rekindled with the advent of nanoscience. Injectable bone cements made with calcium sulfate (CS) are of significant interest, owing to its compatibility and optimal self‐setting property. Its rapid resorption rate, lack of bioactivity, and poor mechanical strength serve as a deterrent for its wide application. Herein, a significantly improved CS‐based injectable bone cement (modified calcium sulfate termed as CSmod ), reinforced with various concentrations (0–15%) of a conductive nanocomposite containing gold nanodots and nanohydroxyapatite decorated reduced graphene oxide (rGO) sheets (AuHp@rGO), and functionalized with vancomycin, is presented. The piezo‐responsive cement exhibits favorable injectability and setting times, along with improved mechanical properties. The antimicrobial, osteoinductive, and osteoconductive properties of the CSmod cement are confirmed using appropriate in vitro studies. There is an upregulation of the paracrine signaling mediated crosstalk between mesenchymal stem cells and human umbilical vein endothelial cells seeded on these cements. The ability of CSmod to induce endothelial cell recruitment and augment bone regeneration is evidenced in relevant rat models. The results imply that the multipronged activity exhibited by the novel‐CSmod cement would be beneficial for bone repair. Abstract : Nanocomposites containing gold nanodots and hydroxyapatite decorated on reduced graphene oxide are prepared using a hydrothermal process. The composites are incorporated in calcium sulfate powder to fabricate an injectable bone cement. The reinforced bone cement possesses improved physical, antibacterial, and mechanical properties. Through upregulation of crosstalk between stem cells and endothelial cells, the injectable cement facilitates vascularized bone regeneration.